Empirical prediction of blast-induced vibration on adjacent tunnels - Wenxin Li; Wenxin Li; Xiao Wang; Lianjun Chen; Chunguang Wang; Jinxiao Liu (Frontiers in Ecology and Evolution, 2023)
The blast-induced vibration during excavation by the drilling and blasting method has an important impact on the surrounding buildings/structures and auxiliary equipment. In particular, with the development of tunnel engineering, the impact of blasting vibration on tunnel construction has attracted extensive attention. Based on literature data statistics, this paper first explored the performance of several commonly used empirical equations in predicting the propagation and attenuation characteristics of blasting vibration on adjacent tunnels. Secondly, the relationships between the empirical parameters of the blasting vibration prediction equation and the geological strength index (GSI) of tunnel surrounding rock were discussed, and two new blasting vibration prediction equations based on site rock GSI were established to approximately predict blast-induced vibration on adjacent tunnels. Finally, the application feasibility of the established prediction equation in practical engineering was discussed based on field test data. The research results show that under the condition of multiple groups of data, the prediction performance of various prediction models does not differ significantly. With the increase of the GSI of the surrounding rock mass of the adjacent tunnel, the site coefficients β and k of the blasting vibration prediction equation in predicting PPV (peak particle velocity, resultant velocity) both show a decreasing trend as a whole. The site coefficient k is generally within 3,000. Two new empirical prediction equations of blasting vibration propagation and attenuation on adjacent tunnels under different site conditions were established: Eq. (14) for PPV and Eq. (15) for PPVi (max) (maximum value of the three component velocities; i = x, y, z represent peak component particle velocity). The verification analysis of five sites shows that these two equations have a certain practical application value. Compared with other empirical equations, these two equations do not need regression fitting blasting vibration data, they only used the GSI of the site rock mass, and they are more easy to use in the field when there is a lack of monitoring data.